Biochemical analysis of a papain-like protease isolated from the latex of Asclepias curassavica L. - Liggieri, Constanza Silvina (2009)
Most of the species belonging to Asclepiadaceae family usually secrete an endogenous milk-like fluid in a network of laticifer cells in which sub-cellular organelles intensively synthesize proteins and secondary metabolites. A new papain-like endopeptidase (asclepain cII) has been isolated and characterized from the latex extracted from petioles of Asclepias curassavica L. (Asclepiadaceae). Asclepain cII was the minor proteolytic component in the latex, but showed higher specific activity than asclepain cI, the main active fraction previously studied. Both enzymes displayed quite distinct biochemical characteristics, confirming that they are different enzymes. Crude extract was purified by cation exchange chromatography (FPLC). Two active fractions, homogeneous by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and mass spectrometry, were isolated. Asclepain cII displayed a molecular mass of 23,590 Da, a pI higher than 9.3, maximum proteolytic activity at pH 9.4-10.2, and showed poor thermostability. The activity of asclepain cII is inhibited by cysteine proteases inhibitors like E-64, but not by any other protease inhibitors such as 1,10-phenantroline, phenylmethanesulfonyl fluoride, and pepstatine. The N-terminal sequence (LPSFVDWRQKGVVFPIRNQGQCGSCWTFSA) showed a high similarity with those of other plant cysteine proteinases. When assayed on N-α-CBZ-amino acid-p-nitrophenyl esters, the enzyme exhibited higher preference for the glutamine derivative. Determinations of kinetic parameters were performed with N-α-CBZ-l-Gln-p-nitrophenyl ester as substrate: Km = 0.1634 mM, kcat = 121.48 s-1, and kcat/Km = 7.4 × 105 s-1/mM.